The Effect Shopee’s Flash Sale Program on Consumers’ Purchase Decisions in Wara District, Palopo City - Putu Indra Susila; Nurjannah Nurjannah; Cici Mahmut; Nurul Aulia Putri; Sabila Putri (Teewan Journal Solutions, 2026)
This study aims to analyze the effect of Shopee's Flash Sale program on consumers' purchase decisions in Wara District, Palopo City. The study employed a quantitative approach using a survey method. The population consisted of residents who had purchased products through Shopee's Flash Sale program, while the sample comprised 50 respondents selected using the accidental sampling technique. Data were collected through observation, interviews, and questionnaires using a Likert scale. The data were analyzed using simple linear regression with the assistance of SPSS software, including validity, reliability, classical assumption, and hypothesis testing. The results indicate that Shopee's Flash Sale program has a positive and significant effect on consumers' purchase decisions. This is evidenced by a calculated t-value of 16.031, which exceeds the t-table value of 2.011, with a significance level of 0.000 (<0.05), and a regression coefficient of 0.972. These findings suggest that the more attractive Shopee's Flash Sale program is, the greater the likelihood that consumers will make purchase decisions. This study is expected to provide valuable insights for e-commerce businesses in developing more effective promotional strategies and to serve as a reference for future research.